The management of political risk - Giambona, Erasmo; Graham, John R; Harvey, Campbell R (Journal of International Business Studies, 2017)
We explore a long-standing prediction in the international business literature that managers’ subjective perceptions of political risk – not just the level of risk – are important for how firms manage political risk. The importance attributed to political risk by corporate executives has increased over the last 15 years and our results show that political risk is now considered more important than commodity (input) risk. Our analysis suggests that nearly 50% of firms avoid (not simply reduce) foreign direct investment because of political risk. Using a unique survey-based psychometric evaluation of manager risk aversion, we show that firms with risk averse executives are more likely to avoid investment in politically risky countries – a key implication of behavioral models. This relation is economically stronger when agency problems are more likely to be severe: for example, when executives are less aligned with shareholder value maximization, and when executives are younger (and therefore might put their personal career concerns in front of shareholders’ interests). While numerous studies have shown that political risk affects foreign direct investment using objective measures of such risk (electoral uncertainty, conflicts, etc.), our study documents that executives’ subjective perceptions of political risk are also important for political risk management.